Antarctic ozone hole modifies iodine geochemistry on the Antarctic Plateau ... : ثقب الأوزون في أنتاركتيكا يعدل الكيمياء الجيولوجية لليود في هضبة أنتاركتيكا ... - Andrea Spolaor; François Burgay; Rafael P. Fernández; Clara Turetta; Carlos A. Cuevas; Kitae Kim; Douglas E. Kinnison; Jean‐François Lamarque; Fabrizio De Blasi; Elena Barbaro; Juan Pablo Corella; Paul Vallelonga; et al. (OpenAlex, 2021)
Abstract Polar stratospheric ozone has decreased since the 1970s due to anthropogenic emissions of chlorofluorocarbons and halons, resulting in the formation of an ozone hole over Antarctica. The effects of the ozone hole and the associated increase in incoming UV radiation on terrestrial and marine ecosystems are well established; however, the impact on geochemical cycles of ice photoactive elements, such as iodine, remains mostly unexplored. Here, we present the first iodine record from the inner Antarctic Plateau (Dome C) that covers approximately the last 212 years (1800-2012 CE). Our results show that the iodine concentration in ice remained constant during the pre-ozone hole period (1800-1974 CE) but has declined twofold since the onset of the ozone hole era (~1975 CE), closely tracking the total ozone evolution over Antarctica. Based on ice core observations, laboratory measurements and chemistry-climate model simulations, we propose that the iodine decrease since ~1975 is caused by enhanced iodine ... : انخفض الأوزون الستراتوسفيري القطبي منذ السبعينيات بسبب الانبعاثات البشرية لمركبات الكلوروفلوروكربون والهالونات، مما أدى إلى تكوين ثقب الأوزون فوق القارة القطبية الجنوبية. آثار ثقب الأوزون والزيادة المرتبطة بها في الأشعة فوق البنفسجية الواردة على النظم الإيكولوجية البرية والبحرية راسخة ؛ ومع ذلك، فإن التأثير على الدورات الجيوكيميائية للعناصر النشطة ضوئيًا في الجليد، مثل اليود، لا يزال في الغالب غير مستكشف. هنا، نقدم أول سجل لليود من هضبة أنتاركتيكا الداخلية (القبة C) التي تغطي حوالي 212 سنة الماضية (1800-2012 م). تظهر نتائجنا أن تركيز اليود في الجليد ظل ثابتًا خلال فترة ما قبل ثقب الأوزون (1800-1974 م) لكنه انخفض شقين منذ بداية عصر ثقب الأوزون (~1975 م)، وتتبع عن كثب تطور الأوزون الكلي فوق القارة القطبية الجنوبية. بناءً على ملاحظات قلب الجليد والقياسات المختبرية ومحاكاة نموذج الكيمياء والمناخ، نقترح أن انخفاض اليود منذ ~1975 ناتج عن زيادة إعادة انبعاث اليود من الكتل الثلجية بسبب الزيادة التي يحركها ثقب الأوزون في الأشعة فوق البنفسجية التي تصل إلى هضبة أنتاركتيكا. تشير هذه النتائج إلى إمكانية أن تكون سجلات ...